2011
DOI: 10.1074/jbc.m111.227546
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants within N Terminus of Orai3 Protein That Control Channel Activation and Gating

Abstract: STIM1 and Orai represent the key components of Ca2+ release-activated Ca2+ channels. Activation of Orai channels requires coupling of the C terminus of STIM1 to the N and C termini of Orai. Although the latter appears to be central in the interaction with STIM1, the role of the N terminus and particularly of the conserved region close to the first transmembrane sequence is less well understood. Here, we investigated in detail the functional role of this conserved region in Orai3 by stepwise deletions. Molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 35 publications
2
59
0
3
Order By: Relevance
“…24−26 One of these studies reports on repeated functionalization of the identical chip with different biotinylated peptides. 24 It was not clear, however, whether this method is also applicable to statistically biotinylated proteins; therefore, this important question was examined in the present study (see Results section).…”
Section: ■ Introductionmentioning
confidence: 98%
“…24−26 One of these studies reports on repeated functionalization of the identical chip with different biotinylated peptides. 24 It was not clear, however, whether this method is also applicable to statistically biotinylated proteins; therefore, this important question was examined in the present study (see Results section).…”
Section: ■ Introductionmentioning
confidence: 98%
“…No binding of CaM was observed with truncated Orai3 lacking aa46-51 ( Figure S4 d), in line with the reported loss of CDI. [7] In the absence of Ca 2+ ,n o interaction of CaM was detected with any Orai peptide (open squares in Figure 1), indicating specific Ca 2+ -dependent binding. In order to rule out that two-step binding was induced by the statistical labeling of CaM, we measured the interaction between labeled CaM and the CMBD of smMLCK.…”
Section: Orai1andorai3arecamentioning
confidence: 99%
“…[1][2][3][4] Much less is known about the Ca 2+ -dependent inactivation (CDI) of Orai which is important in the regulation of the intracellular Ca 2+ level. In anumber of studies,calmodulin (CaM) was found to bind to ahighly conserved N-terminal segment of Orai1/3, and to act as an egative regulator of channel function, [5][6][7] although this was lately questioned.…”
Section: Orai1andorai3arecamentioning
confidence: 99%
See 2 more Smart Citations